Influence of Polyvinyl Pyrrolidone on Absorption and Radiation Transitions of Mn\(^2 + \) ions in Mn-doped ZnS Nanoparticles - Thai, Dang Van; Thang, Pham Van; Ben, Pham Van; Van, Bui Hong; Thi, Tran Minh; Nhat, Hoang Nam (Communications in Physics, 2016)
ZnS:Mn nanoparticles were synthesized by co-precipitation method from the precursors solutions of 0.1M Zn(CH\(_3\)COO)\(_2\), Na\(_2\)S and Mn(CH\(_3\)COO)\(_2\) then were capped with polyvinyl pyrrolidone. The XRD patterns showed that the ZnS:Mn nanoparticles possessed the \(T_d^2 - F43m\) cubic structure with the average crystallite size of several nanometers. At 300 K, the obtained photoluminescence spectra showed only a wide yellow-orange band centered at 603 nm, which should be attributed to the radiation transition of [\(^4\)T\(_1(^4\)G)\( → ^6\)A\(_1(^6\)S)] of Mn\(^2 + \)(3d\(^5)\) cations in the ZnS matrix. The excitation spectra recorded at 300 K on the other hand featured a strong photoluminescence band around 310-334 nm, which were assigned to the near band-edge absorption transition of ZnS host lattice, in addition with three weaker bands relating to the absorption transitions of [\(^6\)A\(_1(^6\)S) \( → \) \(^4\)T\(_2(^4\)D)]: 430 nm, [\(^6\)A\(_1(^6\)S) \( → \) \(^4\)A\(_1(^4\)G) – \(^4\)E(\(^4\)G)]: 468 nm, and [\(^6\)A\(_1(^6\)S) \( → ^4\)T\(_2(^4\)G)]: 498 nm of Mn\(^2 + \)(3d\(^5)\) cations. It was shown that the capping affected only the intensities of emissions bands.